Non-invasive assessment of ?-carotene levels in the skin of colombian adults (2012)
Introduction: Carotenoid pigments have antioxidant properties beneficial for human health. Use of resonance Raman spectroscopy (RRS) as a reliable method for measuring carotenoid levels in tissues such as dermis has been suggested. However, data about the variability and reproducibility of this technique should be collected before it can be used. Objective: To assess reproducibility of RRS for detection of total ?-carotene levels in the skin of Colombian adults. Design: Forty-eight healthy men and 30 healthy women with various pigmentation levels were enrolled into the study. Measurements by RRS were performed in the palmar region and medial and lateral aspects of the arms. Odds ratio and 95% confidence intervals were calculated, adjusting for confounding factors: body mass index, waist circumference, percent body fat, age, race, smoking, and sex. Reproducibility of the technique was estimated using intraclass correlation coefficient (ICC). Results: Mean ?-carotene levels were 29.9±11.9 in men and 30.6±8.6 in women (. P=.787). No differences or significant associations were found of ?-carotene levels with confounding factors assessed by sex. ICCs were 0.89 in the palmar region, 0.85 in the medial aspect of arm, and 0.82 in the external aspect of arm. Conclusion: RRS spectroscopy is a reliable method for non-invasive measurement of ?-carotene levels in skin, and may be used as an important biomarker of antioxidant status in nutritional and health studies in humans. © 2012 SEEN.